Το έργο του R. Dawkins: Βιβλιογραφική συμβουλή - Αλεξιάδης Μηνάς (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1984)
May 1985 marks the thirtieth anniversary of the death (1955) of the distinguished British philhellene, hellenist and university professor Richard M. Dawkins. This anniversary offers an occasion for a reappraisal of Dawkins’s contribution to various fields of Greek scholarship (Archaeology, Linguistics, Philology and mainly Folklore). What is primarily needed however is an initial bibliographical codification of the Greekcentered writings of the English scholar. The composition of a complete bibliography of Dawkins is not an easy task. He was an erudite and prolific author whose writings include, besides the main body of his work, a great number of essays and articles published in Greek and international learned journals (some of them rare today), in honorary volumes, and newspapers. That is one of the reasons why the present work, as a first attempt at a comprehensive bibliography focuses only on his Greek -centered publications (which constitute the greatest part of his writings), ommiting works whose themes relate to international scholarship. For instance, his work on the writer Norman Douglas, which was first published in Florence in 1933 (second edition: London 1952), is not listed in the bibliography. General works however are few in number and not among his most important ones. The works are presented in chronological order and classified by scholarly discipline. Book reviews and book notes are also listed. Articles (both in encyclopaedias and elsewhere), essays and obituaries written about the English scholar are included in an Appendix.